2017
DOI: 10.1016/j.jconrel.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Combination of nitric oxide and drug delivery systems: tools for overcoming drug resistance in chemotherapy

Abstract: Chemotherapeutic drugs have made significant contributions to anticancer therapy, along with other therapeutic methods including surgery and radiotherapy over the past century. However, multidrug resistance (MDR) of cancer cells has remained as a significant obstacle in the achievement of efficient chemotherapy. Recently, there has been increasing evidence for the potential function of nitric oxide (NO) to overcome MDR. NO is an endogenous and biocompatible molecule, contrasting with other potentially toxic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
131
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 78 publications
1
131
0
2
Order By: Relevance
“…However, if the results of Allenbach and coworkers suggesting that the inducible NOS/nitric acid axis plays a role in the repair of damaged muscle in myositis patients are confirmed, this observation could be truly exciting with respect to new therapeutic strategies. Recent work by others suggesting that novel new strategies for therapeutically delivering nitrous oxide to damaged tissue in a clinical setting may be on the horizon (51)(52)(53).…”
Section: Further Perspective On the Studies Of Allenbach And Coworkersmentioning
confidence: 99%
“…However, if the results of Allenbach and coworkers suggesting that the inducible NOS/nitric acid axis plays a role in the repair of damaged muscle in myositis patients are confirmed, this observation could be truly exciting with respect to new therapeutic strategies. Recent work by others suggesting that novel new strategies for therapeutically delivering nitrous oxide to damaged tissue in a clinical setting may be on the horizon (51)(52)(53).…”
Section: Further Perspective On the Studies Of Allenbach And Coworkersmentioning
confidence: 99%
“…been reported that the clearance effect of NO by cancer cells is closely related to its concentration and release rate. [14] However, NO molecules feature a short half-life in vivo and is prone to react with bio-macromolecules and free radicals, so it is difficult for NO to achieve effective enrichment in tumor region. Therefore, developing external-responsive and local-triggered NO donors can be employed for on-demand NO release.…”
mentioning
confidence: 99%
“…It has been reported that NO within the concentration range of 1 mm-1 mm can yield direct anticancer effects with few adverse effects,b ut higher concentrations (> 1mm)m ay cause NO poisoning. [12] Additionally,t he NO release rate is also avery important factor for the functions of NO.Although it is the generated NO concentration (rather than NO release rate) that may be an important determinant in whether NO can mediate the cancer cell death, [13] faster NO release will yield as tronger cancer cell-killing effect than slower NO release under the conditions of similar total NO concentrations.Overall, the functions of NO are closely associated with the NO-releasing characteristics/concentrations that can be determined by NO donors and the tumor microenvironment (TME). [12a] Therefore,s timuli-responsive NO donors are highly desired for releasing NO in ac ontrolled manner for on-demand cancer therapy with very little systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%